Intellectual Property Rights Violations in Data Generated by Artificial Intelligence: A Comparative Analysis between Indonesian Law and International Practices - Ismail Koto; Rahimah (Kosmik Hukum, 2025)
This article examines the issue of intellectual property rights (IPR) violations arising from the use of Artificial Intelligence (AI) in generating creative works. While AI technologies have advanced rapidly and are capable of producing outputs comparable to human creations, legal frameworks remain underdeveloped. Some jurisdictions restrict copyright ownership to humans, while others explore whether AI or its owners may hold rights. The Indonesian Copyright Law (Law No. 28/2014)¹ does not explicitly regulate AI-generated works, resulting in a legal vacuum. This study adopts a normative legal research method with statute, comparative, and case approaches to analyze Indonesia’s regulatory gaps alongside practices in the United States, European Union, and Japan. Findings show that Indonesian law remains limited to conventional notions of human authorship, while international cases such as Thaler v. Copyright Office² and Getty Images v. Stability AI³ illustrate ongoing disputes about AI creativity and copyright. The article contributes by proposing policy reforms in Indonesia, emphasizing the need for adaptive legislation, clearer liability mechanisms, and harmonization with global standards. Implications: Strengthening protection for creators, ensuring fair use of data in AI training, and advancing international dialogue on AI’s legal status.